Acute malnutrition and its determinants of preschool children in Bangladesh: gender differentiation - Md. Reazul Karim; Abu Sayed Md. Al Mamun; Md. Masud Rana; Rashidul Alam Mahumud; Nurun Naher Shoma; Dhiman Dutt; Premananda Bharati; Md. Golam Hossain (BMC, 2021)
Abstract Background Children acute malnutrition (AM) is a global public health concern, especially in low and middle income countries. AM is associated with multiple physiological vulnerabilities, including immune dysfunction, enteric barrier disruption, gut microbiome dysbiosis, and essential nutrient deficits. This study aimed to determine the prevalence of AM and its associated factors among preschool children in Rajshahi district, Bangladesh. Methods This cross-sectional study was conducted from October to December, 2016. Children acute malnutrition was assessed using mid-upper arm circumference. Multiple binary logistic regression analyses were employed to determine the associated factors after adjusting the effect of independent factors of children AM. Result The prevalence of AM amongst preschool children was 8.7%, among them 2.2 and 6.5% were severe acute malnutrition and moderate acute malnutrition, respectively. Z-proportional test demonstrated that the difference in AM between girls (11.6) and boys (5.9%) was significant (p < 0.05). Children AM was associated with being: (i) children aged 6-23 months (aOR = 2.29, 95% CI: 1.20-4.37; p < 0.05), (ii) early childbearing mothers' (age < 20 years) children (aOR = 3.06, 95% CI: 1.08-8.66; p < 0.05), (iii) children living in poor family (aOR = 3.08, 95% CI: 1.11-8.12; p < 0.05), (iv) children living in unhygienic latrine households (aOR = 2.81, 95% CI: 1.52-5.09; p < 0.01), (v) Hindu or other religion children (aOR = 0.42, 95% CI: 0.19-0.92; p < 0.05). Conclusion The prevalence of AM was high among these preschool children. Some modifiable factors were associated with AM of preschool children. Interventions addressing social mobilization and food security could be an effective way to prevent acute malnutrition among children in Bangladesh.